Computer simulation of steady state and transient performance for permanent magnet DC motors - Wing, Mitchell (Department of Electrical Engineering, 2016)
Permanent magnet motors have outstanding performance for applications such as industrial robots, computer peripherals and automobiles. Since these motors are being used in a growing number of applications, the techniques used to model them are becoming more important in an attempt to obtain the best possible performance from any new design. The objective if this thesis is to develop an understanding of the classical and the finite element theory in an attempt to obtain the full characteristics of small commutator permanent magnet direct current motors. A comparison of the two methods is done in an attempt to obtain the most effective method of designing new motors. The comparison is done by calculating the performance of two segmental magnet de motors using the two methods. The methods are investigated separately to ensure that the best possible results are obtained from the simulations. The comparison of the steady state and transient characteristics of the motors are done separately.